Mies van der Rohe, der Werkbund und die Frage der Technik um 1930 - Freigang, Christian (RIHA Journal, 2018)
This paper examines the ways Mies van der Rohe has dealt with the phenomenon of mechanization of all areas of human life, that ever since the mid-twenties was becoming an increasingly controversial political issue. Building on a number of philosophical essays on the role of modern large-scale technology, especially those by Friedrich Dessauer, Mies advanced a strategy that can be described as the aesthetic transcendence of industrially-produced technical items. By positioning his architecture in this manner, he warded off all accusations of purely economically-motivated rationalism. What Mies considered to be a “spiritual” approach to architecture has also defined the program of the Werkbund that he presided at that time and has laid the foundation for his postwar work.